Produção de mudas e crescimento de Eucalyptus grandis Hill ex maiden inoculado com fungos ectomicorrízicos em área arenizada - Souza, Eduardo Lorensi de (2009)
Eucalyptus. grandis is one of the main species used in forestry, in the Rio Grande do Sul State. The reforestations have been concentrated in low fertility soil areas, especially in phosphorus, such as the Quartzarenic Neosoils, which occur in the south of the state. It represents a problem for the establishment of this culture in field. This forestry species has the capacity of making symbiosis with ectomycorrhizal fungi that increase plant grown and the absorption of water and nutritious. The aim of the work was to evaluate the initial growth of eucalyptus in sandy area and the ectomycorrhizal fungi inoculation isolated, individually or mixed in Neosoil. In the first stage, eucalyptus seedlings were produced in greenhouse, inoculated or no-inoculated with the UFSC-Pt116 isolated, produced in peat or in Neosoil. After 120 days seedlings were transplanted to an area subjected to the process of sanding in São Francisco de Assis and evaluated regarding the survival, height, stem s diameter and tenors of nitrogen, phosphorus and potassium, total phosphorus, inorganic phosphorus, and wood production. In the second stage it was tested, in greenhouse, the effect of ectomycorrhizal fungi inoculation with the UFSC-Pt116, UFSC-Pt188 and UFSC-SA9 isolates, individually or mixed in peat substrate and in Neosoil. Determinations were accomplished regarding stem s diameter and height, dry matter of the aerial portion and the roots, roots volume, mycorrhizal colonization as well as the level of nitrogen, potassium and total, organic and inorganic phosphorus of the aerial portion of plants. In field, the plants produced in Neosoil and inoculated with the isolated UFSC-Pt116 obtained the highest survival, stem s height and diameter, nitrogen level, as well as wood production in relation to the no-inoculated seedlings. In the second study, the plants that received individual inoculation of the isolated UFSC-Pt116 and UFSC-SA9 and that were produced with peat obtained the highest height, stem s diameter, mycorrhizal colonization and dry matter accumulation. The plants that were produced in Neosoil and the individually inoculated with the isolated UFSC-Pt116, UFSC-Pt118 and UFSCSA9 showed highest height, stem s diameter, dry matter of the aerial portion and roots volume. The seedlings produced in Neosoil obtained higher height and diameter than those produced in peat.